Feminist Perspectives on Social Work and Human Sexuality ... - Heyworth, Elspeth (Canadian Woman Studies/les cahiers de la femme, 1987)
Mary Valentich and James Gripton, eds. Journal of Social Work and Human Sexuality, 3, 2/3 (1985)